Novel coronavirus SARS-CoV-2 in the context of global epidemiology of coronavirus infections - M. V. Supotnitskiy (Вестник войск РХБ защиты)
The seemingly unexpected appearance of SARS-CoV-2 in China and its subsequent rapid spread throughout the world make us think seriously about the coronavirus threat emanating from natural foci in the territory of our country. The aim of this work is to study SARS-CoV-2 in the context of real global epidemiology of coronavirus infections. The data of Chinese scientists, published in Englishlanguage scientific journals, has been used during the preparation of the article. Their analysis showed the vast spread of viruses of this taxon among bats and hedgehogs in the natural ecosystems of Europe as well. To date the host of SARS-CoV-2 virus, intermediate between bats and humans, as well as the intermediate coronavirus, the direct predecessor of SARS-CoV-2, have not been detected. The bulk of the coronavirus genome is conservative, but it appears to be extremely prone to genetic recombination in vivo, so the virus can be redirected both in natural and artificial conditions from wild animals to humans by changing the structure of the S1 protein. The pathogenesis of coronavirus infections in humans that causes severe acute respiratory syndrome (SARS), include the specific recognition of receptors on target cells in the lower parts of human lungs, the penetration of the virus into the target cells, viral replication, generation of cytokine responses, that destroy the lower parts of the lungs, and the appearance of the phenomenon of antibody-dependent enhancement of the infection, that results in generalized spread of the virus. The virulence of SARS-CoV-2 for humans is significantly lower than that of the coronaviruses that caused SARS in 2002–2003 in China and the Middle East respiratory syndrome in the Middle East in 2012. However, due to the higher stability of the virus when penetrating the endosomes of the cell and the effectiveness of the replication/transcription complex, the virus replicates to large enough numbers to transmit easily from ill people to healthy. Different ethnic groups have different sensitivity to SARS-CoV-2 because of the different amounts of ACE2 receptors on the surface of type II pneumocytes. The article also sketches certain clinical observations made by Chinese researchers during an outbreak of coronavirus infection caused by SARS-CoV-2. The author states, that effective and timely diagnosis of COVID-19 is possible only by the combination of molecular diagnostics of SARS-CoV-2 and the detection of characteristic pneumonic foci by computed tomography.